Global transcriptome and coexpression network analyses reveal cultivar-specific molecular signatures associated with different rooting depth responses to drought stress in potato - Qin, Tianyuan; Ali, Kazim; Wang, Yihao; Dormatey, Richard; Yao, Panfeng; Bi, Zhenzhen; Liu, Yuhui; Sun, Chao; Bai, Jiangping (Frontiers in Plant Science, 2022)
Root response to drought stress is an intricate process regulated via a complex transcriptional regulatory network. To understand molecular mechanisms governing root response to drought stress and rooting depth in potato, transcriptome dynamics of roots in different stages of drought stress were analyzed in deep- (C119) and shallow-rooting (C16) cultivars. Stage-specific expression was observed for a significant proportion (>11%) of genes in each cultivar. Compared with C16, approximately half the genes were significantly differentially expressed in C119. Modules of coexpressed genes were associated with root responses to different stages of drought stress. In a comparative analysis, some modules were different between the two cultivars and were associated with differential responses to specific drought stress stages. Transcriptional regulatory networks were constructed, and key components that determined rooting depth were identified. Rooting depth (shallow vs deep) was largely determined by plant-type cell wall organization or biogenesis, cell wall organization or biogenesis, hemicellulose metabolic process, and polysaccharide metabolic process. In addition, candidate genes responding to drought stress were identified in deep and shallow rooting potato varieties. The results of this study are a valuable resource for further investigations on roles of candidate genes that affect rooting depth and drought tolerance mechanisms in potato.